DEVELOPMENT AND VALIDATION OF THE TAIWAN CHILDREN’S ENVIRONMENTAL ACTION INDEX - Yen, Chiung-Fen; Chiang, Chia-Ling; Hou, Li-Hua; Yao, Tsung-Wei; Su, Chiu-Ju; Mintzes, Joel J. (European Scientific Journal, ESJ, 2015)
In this study, we use Smith-Sebasto & Fortner’s (1994) Environmental Action Internal Control Index (EAICI) as a framework to develop, and validate a useful instrument for assessing environmental attitudes and behavior among elementary and middle school children within the Taiwanese context. We dub the new instrument the Taiwan Children’s Environmental Action Index (TCEAI). Our findings suggest that the TCEAI displays substantial internal consistency (Cronbach's alpha=.92), moderately positive correlations with self-report measures of environmentally responsible behavior (R = .35 to .46, p < .01), and few threats to validity by age or gender. The results suggest that the TCEAI may be used to elicit important dimensions of environmental attitudes and to predict environmentally responsible behavior for elementary and middle school children in Taiwan. Practical implications are discussed.